2007
DOI: 10.1016/j.socscimed.2006.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Professional accounts of electroconvulsive therapy: A discourse analysis

Abstract: Electroconvulsive therapy (ECT) is a socially contested psychiatric intervention. However, the accounts of professionals involved in its use have rarely been systematically investigated.This study aimed to examine the accounts of clinicians who have used ECT on a routine basis. Eight health professionals (psychiatrists, anaesthetists and psychiatric nurses) with experience of ECT administration were interviewed about the procedure. Discourse Analysis was used to interpret the interview transcripts. Interviewee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Cooper and (1999) and he felt that this had encouraged him to want to publish (something he eventually did: Stevens and Harper, 2007). However, Julia, Peter and Phil were also tired at the end of a demanding training and felt that they needed a break.…”
Section: Dissemination Dissemination Disseminationmentioning
confidence: 99%
“…Cooper and (1999) and he felt that this had encouraged him to want to publish (something he eventually did: Stevens and Harper, 2007). However, Julia, Peter and Phil were also tired at the end of a demanding training and felt that they needed a break.…”
Section: Dissemination Dissemination Disseminationmentioning
confidence: 99%
“…Researchers have therefore suggested that clinical psychologists' conceptualizations of mental health have significant clinical implications for their work with service users (Hugo, 2001;Stevens & Harper, 2007).…”
mentioning
confidence: 99%
“…The synthesis which emanates, known as 'critical discursive psychology', Wetherell (1998) and Edley (2001) argue, will allow for a more integrated approach to discourse analysis that can respond to criticisms of both discursive psychology and FDA. As a result, critical discursive psychology (Edley & Wetherell, 1999, 2001Stevens & Harper, 2007;Wetherell, 1998) was chosen as the most appropriate method in addressing the research as within this approach the analysis consists of an examination of the local organisation of talk, as well as the organisation of the broad, social and culturally resonant interpretative resources the participants draw upon (Edley & Wetherell, 2001).…”
Section: Methodsmentioning
confidence: 99%